2009
DOI: 10.1021/ja9060883
|View full text |Cite
|
Sign up to set email alerts
|

Direct Raman Measurement of an Elevated Base pKa in the Active Site of a Small Ribozyme in a Precatalytic Conformation

Abstract: Catalytic RNA molecules can achieve rate acceleration by shifting base pK(a) values toward neutrality. Prior evidence has suggested that base A38 of the hairpin ribozyme plays an important role in phosphoryl transfer, possibly functioning as a general acid, or by orienting a specific water molecule for proton transfer. To address the role of A38, we used Raman spectroscopy to measure directly the pK(a) of the N1-imino moiety in the context of hairpin ribozyme crystals representative of a "precatalytic" conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 26 publications
4
62
1
Order By: Relevance
“…Hence, the lack of an effective base and an effective acid and an increase of the energy of the transition state are possibly responsible for the sixth order of magnitude decrease in the cleavage rate of the G40A mutant in the presence of GlcN6P. Therefore, our results suggest that the general acid (the amine group of GlcN6P) has a pK a of about 6 and the general base (if G is the base) has a pK a of about 9.2, similar to the possibility in the hairpin ribozyme, with pK a s of 5.4 (A38; the acid) and 9.5 (Guo et al 2009; Ferre-D'Amare 2010), respectively.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Hence, the lack of an effective base and an effective acid and an increase of the energy of the transition state are possibly responsible for the sixth order of magnitude decrease in the cleavage rate of the G40A mutant in the presence of GlcN6P. Therefore, our results suggest that the general acid (the amine group of GlcN6P) has a pK a of about 6 and the general base (if G is the base) has a pK a of about 9.2, similar to the possibility in the hairpin ribozyme, with pK a s of 5.4 (A38; the acid) and 9.5 (Guo et al 2009; Ferre-D'Amare 2010), respectively.…”
Section: Resultssupporting
confidence: 66%
“…2;Hampel and Tinsley 2006;Klein and Ferre-D'Amare 2006;Cochrane et al 2007Cochrane et al , 2009). The general acid-base catalytic mechanism has been extensively studied (Thompson and Raines 1994;Breslow and Chapman 1996;Sowa et al 1997;Bevilacqua 2003;Emilsson et al 2003;Bevilacqua et al 2004;Lonnberg and Lonnberg 2005;Bevilacqua and Yajima 2006) and is common in both protein (Thompson and Raines 1994;Breslow and Chapman 1996;Sowa et al 1997) and nucleic acid chemistry (Nakano et al 2000;Han and Burke 2005;Guo et al 2009). In glmS, the proposed cleavage mechanism is similar to that of other self-cleaving ribozymes, in which cleavage is initiated by the binding of GlcN6P.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poisson-Boltzmann calculations (Tang et al 2007) and Raman spectroscopy (Guo et al 2009) have shown that A38 has an elevated pK a (pK a values of 5.9 and 5.46, respectively), consistent with the observed pH dependence of activity arising from proton transfer at this nucleobase. Exogenous base rescue and substitution with other nucleobases have demonstrated the importance of both the N1 and N6 of A38 for full activity (Kuzmin et al 2005).…”
Section: Does the Hairpin Ribozyme Share The Same Catalytic Mechanism?supporting
confidence: 57%
“…NMR with isotopically labeled RNAs and, more recently, Raman crystallography have been used to measure microscopic pK a values for protonation of N3 of pyrimidines and N1 of purines in catalytic RNAs (42,47,48,51). NMR analyses of A38 protonation in an isolated loop B domain of the Hp Rz gave a pK a value of 4.89 (40).…”
Section: Discussionmentioning
confidence: 99%